The Use of a Recombinant Canarypox-Based Equine Influenza Vaccine during the 2007 Australian Outbreak: A Systematic Review and Summary - Paillot, Romain (Pathogens, 2016)
In 2007, Australia experienced the most extensive equine influenza outbreak observed in recent years. Extraordinary measures were rapidly implemented in order to control and prevent the spread of this highly contagious disease. The control strategy involved stringent movement restriction and disease surveillance, seconded by emergency post-outbreak vaccination strategies. Sixteen months after the first case and 12 months following the last reported case, Australia regained its equine influenza-free OIE status. This systematic review reports and summarises information relating to the implementation of emergency vaccination during the 2007 Australian equine influenza outbreak, including the choice of vaccine and implementation strategies.